VD_FINDINFO AP / 2009 / 38 vom 4. Dezember 2007 - VD Tribunal cantonal (2007)
ASSOCIATION, ASSEMBLÉE GÉNÉRALE, DROIT DE VOTESOCIÉTÉ, EXERCICE DU DROIT DE VOTE, MAJORITÉ ABSOLUE, MAJORITÉ RELATIVE, DÉCISIONDROIT PRIVÉ, POUVOIR D'EXAMEN, QUESTION DE FAIT | 64 al. 1 CC, 64 al. 2 CC, 64 CC, 67 al. 2 CC, 67 CC, 68 CC, 75 CC, 452 al. 1ter CPC, 456a al. 2 CPC, 456a CPC